Islamizing Human Housing and Settlement: Integrating Islamic Principles in Sustainable Real Estate Development - Mat Noor, Noorsidi Aizuddin; Diana Derisb, Farhana; Mokhtar, Afizan (Universitas Darussalam Gontor, 2025)
This research explores the equitable, balanced, and environmentally sound application of Islamic provisions to real estate to create healthier societies. It stands on the basics of Islamic teachings on moderation, fairness, and the general leadership of the community, which are in harmony with the philosophy of modern sustainable action. This research used both quantitative and qualitative research methods, where information from the developers and planners was obtained through interviews while quantitative information from the inhabitants of sustainable communities was obtained through a survey. The research shows that whereas best practices regarding environmental endowment have been implemented properly in real estate-related projects, other Islamic values, for instance equity and social justice, as well as integration of the community, have not been so well implemented appropriately. They also noted a significant and positive relationship between the perceived degree of satisfaction with community spaces and the perceived degree of Islamic values integration. This led to the identification of challenges such as the insufficient practical experience of developers in implementing Islamic finance instruments that comprise sukuk and waqf, among others. These studies indicate the need to focus on raising awareness and capacity to enable developers to adhere to Islamic guidelines more effectively. The research has implications that policymakers and developers need to take into consideration in the designing of future real estate developments with the aim of achieving fairness in economics and enhancing the welfare of communities. It is recommended that subsequent studies examine these gaps and analyse the potential social repercussions of the Islamic-based real estate projects.